Laboratorijska diagnostika covid-19 - Omersel, Jasna (Farmacevtski vestnik, 2020)
In the fight against covid -19, countries where extensive laboratory testing, consistent monitoring and isolation of infected individuals were implemented have been incomparably more successful. Laboratory diagnostics contributes to faster and more efficient medical decisions. Its role is to select the best methods available at a given time, and to provide high quality and reliable results in the shortest possible time. Herein, we present the latest findings on the immune response to a SARS-CoV-2 infection, approaches in the diagnosis of viral infections and the characteristics of a good diagnostic method. We present the diagnostics of covid-19 from recognising active (viral RNA) and past infection (antibodies against viral antigens) to changes in biochemical parameters and the applicability of diagnostic results for successful management of the SARS-CoV-2 pandemic.
Keywords: diagnostika SARS-CoV-2; Imunski odziv; molekularne metode; serološki testi; Zakonodaja